Comparative analysis of functionality in automated payroll accounting in cloud-based accounting applications ("Journal "U". Economy. Management. Finance.", 2025)
The range of use of digital tools in accountance constantly grows. Developers of specialized computer software offer new opportunities to automatize accounting procedures, which gradually alters the format and nature of the bookkeeper’s job. A significant trend in this respect is automation of accounting and analytical support oriented on the accounting policy implementation in what concerns staff labor renumeration on the basis of innovative information technologies, cloud computing among them.The author of the article analyzes the functionality of popular online applications destined for payroll accounting, however from the methodological and applied standpoints; he makes a generalization of benefits and drawbacks of the cloud-based format in the accounting procedures associated with the wage payroll, calculation and registration under the conditions of the up-to-date state of rules and regulations. In reliance on the studied samples of profile online services, the author has developed a universal set of modules for a typical cloud-based application destined for payroll accountance and outlined the limits of using such cloud-based resources in bookkeeping
Keywords: accountancy digitalization; accounting automation; payroll accounting; cloud-based computing; cloud-based applications